Chicken skin-derived collagen peptides chelated zinc promotes zinc absorption and represses tumor growth and invasion in vivo by suppressing autophagy - Liu, Tengfei; Zou, Lifang; Ji, Xiaowen; Xiao, Guiran (Frontiers in Nutrition, 2022)
In order to improve the utilization value of chicken by-products, we utilized the method of step-by-step hydrolysis with bromelain and flavourzyme to prepare low molecular weights chicken skin collagen peptides (CCP) (<5 k Da) and characterized the amino acids composition of the CCP. Then we prepared novel CCP–chelated zinc (CCP–Zn) through chelating the CCP with ZnSO4. We found that the bioavailability of CCP–Zn is higher than ZnSO4. Besides, CCP, ZnSO4 or CCP–Zn effectively repressed the tumor growth, invasion and migration in a Drosophila malignant tumor model. Moreover, the anti-tumor activity of CCP–Zn is higher than CCP or ZnSO4. Furthermore, the functional mechanism studies indicated that CCP, ZnSO4 or CCP–Zn inhibits the tumor progression by reducing the autonomous and non-autonomous autophagy in tumor cells and microenvironment. Therefore, this research provides in vivo evidence for higher-valued utilizing chicken skin in development of zinc supplement and cancer treatment in the future.